2014
DOI: 10.1128/jcm.01197-14
|View full text |Cite
|
Sign up to set email alerts
|

Psychrobacter sanguinis: an Unusual Bacterium for Nosocomial Meningitis

Abstract: We report the first case of postneurosurgical meningitis due to Psychrobacter sanguinis, identified only by 16S rRNA analysis. Psychrobacter spp. usually live in deep sea environments and cold habitats. Despite a strict questioning of the patient and the medical staff, we did not find the source of this bacterium. CASE REPORT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Therefore, amoxicillin treatment with 4g three times per day was continued until the patient had received 15 days of antimicrobial therapy. The patient experienced a rapid recovery under treatment with no other complications [12].…”
Section: From 2004 To 2008 Human Blood Cultures Yielded Fourmentioning
confidence: 88%
See 4 more Smart Citations
“…Therefore, amoxicillin treatment with 4g three times per day was continued until the patient had received 15 days of antimicrobial therapy. The patient experienced a rapid recovery under treatment with no other complications [12].…”
Section: From 2004 To 2008 Human Blood Cultures Yielded Fourmentioning
confidence: 88%
“…We report a first case in which P. sanguinis was isolated from human blood in Korea. In the six previously reported cases, we didn't detailed review for first reported case and the other three cases due to a lack of information in the literature [11] and two cases with meningitis were described as a probable infection [13] or a definite infection [12]. These cases were confirmed as a single organism with P. sanguinis infection by using molecular methods, and were treated with antibiotics.…”
Section: From 2004 To 2008 Human Blood Cultures Yielded Fourmentioning
confidence: 99%
See 3 more Smart Citations